The Link of Teacher Career Paths on the Distribution of High Qualified Teachers: A Chilean Case Study - Maria del Rosario Rivero (Arizona State University, 2015)
This paper uses rich data of 79,418 elementary teachers from 5,521 schools in Chile to study the extent of teacher sorting and its association with teacher career paths. A complete analysis of ten measures of teacher quality shows that highly qualified teachers are unequally distributed across schools. Some schools present a large concentration of highly qualified teachers while others do not even have a single one. Schools with a low concentration of highly qualified teachers are more likely to be public and rural, have a bigger enrollment of low-income and low-performance students. Thus, it is precisely those schools that are most in need. This paper combines the analysis of teacher sorting with teacher career decisions and finds that teacher career paths are associated with the unequal distribution of teachers. At the start of their careers, less qualified teachers are more likely to teach in rural, public, low-income and low-performance schools. These teachers are then more likely to stay in those schools, while less qualified teachers who start working in high-income and high-performing schools are less likely to stay there compared with highly qualified teachers. Education reforms have recognized the key role of teachers. However, efforts have focused on increasing the quality of the teaching workforce and do not target any specific types of schools. This study discusses the lack of targeted policies and educational inequality, proposes the need for an educational reform.